If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y = 12 + -1y Solving 3y = 12 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 3y + y = 12 + -1y + y Combine like terms: 3y + y = 4y 4y = 12 + -1y + y Combine like terms: -1y + y = 0 4y = 12 + 0 4y = 12 Divide each side by '4'. y = 3 Simplifying y = 3
| 2x+20=70 | | x^2+15x+11=2x-1 | | 5.6-.32x=1.12 | | x^2+10x+18=9 | | 140-2x=34x+20 | | y=0.2187x+15.67 | | 3sinx+cosx=2 | | 12-9x=23-16x | | 57.99+.11x=58.54 | | (5b-3)(2b-6)-(-3+8b)(4b-4)= | | .23x+2.34=6.25 | | 4f-12=16 | | 4x^2-9x+9=7x+2 | | =2+3 | | 112-2x=6x+16 | | 2f+g=13 | | a+4b=18 | | 24-t=18 | | h-14=23 | | 20-1.45=1.15 | | 3(2+x)=10+x | | 4x=3+3x | | x-2-8=3 | | 6v=24 | | t+26=41 | | (x^5+y^2)(x^5-Y^2)= | | 0=8+2y | | 2(123*34)= | | 110=80+2xwidth | | 4x^2-3x+16=0 | | -4.3-.1x=-6.1 | | (5a-1)(6a-3)= |